Empirical Analysis of Financial and Macroeconomic Dynamics on Stock Returns - Ismayanti, Diah; Surti, Surti (Universitas Gorontalo, 2025)
This study examines the influence of financial and macroeconomic factors on stock returns of palm oil companies on the Indonesia Stock Exchange during 2018-2024. Using a panel data analysis of 9 palm oil companies, this study investigates how Earnings Per Share (EPS), Price to Earnings Ratio (PER), Return on Equity (ROE), and inflation affect stock performance in the context of the Indonesian economy. The research methodology applies a causal quantitative approach with data from the IDX quarterly financial reports and BPS inflation data. The sample was selected through a purposive sampling method based on the following criteria: listed on the IDX during the study period, consistency of financial report publication, and completeness of variable data. The strategic position of this sector in the Indonesian economy, which contributes to foreign exchange and rural employment, the importance of understanding its investment dynamics. This study integrates the perspective of development economics, analyzing how capital markets can support national economic development through the palm oil sector. These findings are expected to provide insights for investors, companies, and policy makers.